How does external reference pricing work in developing countries: evidence from Iran - Fatemeh Babaie; Mohammad Hossein Motevalli; Gholamhossein Mehralian; Farzad Peiravian; Nazila Yousefi (Frontiers Media S.A., 2023)
Introduction: Governments apply different pricing policies to ensure public accessibility, availability, and affordability of medicines. In this way, external reference pricing (ERP) because of its easy implementation is used widely across countries. However, ERP is completely path dependent, and it would both bring pros and cons, related to its implementing strategy which makes understanding of its impact in different countries challenging. In this study, we examine the performance of the ERP approach in Iran as a pricing tool.Method: We conducted a cross-sectional descriptive study. Although Iran officially uses a reference country basket for ERP, in this study, we use different reference countries based on socioeconomic comparability, access to their price data, medicine pricing approaches, and pharmaceutical expenditure to examine the effect of reference countries as well as the method performance. Then, an empirical study was applied to a list of selected samples of medicines in the Iranian market to compare their price with our new reference countries. Then, we discuss the performance of ERP process based on the real prices in the Iranian pharmaceutical market.Result: The prices of 57 medicines, which contain about 69.2% of the imported Iran pharma market in value, were compared with their prices in selected reference countries. It was found that 49.1% of prices were more expensive in at least one of the reference countries, and in 21% of products, the average price in Iran was higher than the average price in reference countries.Conclusion: Achieving efficient and fair pricing of pharmaceuticals between and within countries is still a complex conceptual and policy problem that ERP in short term can handle. ERP cannot be considered a perfect tool for pricing alone, although its effectiveness is acceptable. It is expected that using other pricing methods alongside the ERP will improve patients' access to medicines. In Iran, we use value base pricing as the main pricing method for every new molecule. Then, we use other methods such as ERP as a complementary method.